On q-integral transforms and their applications - ALBAYRAK, DURMUŞ; UÇAR, FARUK (My University, 2012)
In this paper, we introduce a q-analogue of the P-Widder transform and give a Parseval-Goldstein type theorem. Furthermore, we evaluate the q-Laplace transform of a product of q-Bessel functions. Several special cases of our results are also pointed out.
Keywords: Matematik; Temel Bilimler (SCI); MATHEMATICS; Natural Sciences (SCI); Analysis; Algebra and Number Theory; Mathematics (miscellaneous); General Mathematics; Physical Sciences; q-Calculus; q-Laplace transform; q-analogue of P-Widder transform and q-Bessel function